Export and import functions (empirical analysis on the example of the Czech Republic) - František Obešlo (European Financial and Accounting Journal, 2017)
This paper focuses on import and export of goods of the Czech Republic. The Czech Republic is very open country in European Union. Ratio of import and export of goods and services to GDP is above European Union average. The goal is to find explanatory variables, which have an influence on import and export of goods and to build robust and economically interpretable models. Models are created by cointegration analysis. The advantage of cointegration analysis and error correction models is avoiding spurious regression and differentiation of short-term and long-term relations. There will be used ARDL approach for building models.
Keywords: C5; F14; 650; Cointegration analysis; Export of goods; Import of goods